AI-empowered promotional video generation - Liu, Chang (Nanyang Technological University, 2022)
Promotional videos are rapidly becoming a popular form of product advertising on E-commerce platforms. The traditional way of producing promotional videos is a time-, skill- and cost-intensive process and thus, usually performed by professional teams. This hinders the production of large-scale video-based promotion campaigns. To address this issue, in this thesis we propose AI-empowered persuasive video generation (AIPVG) that automatically generates promotional videos based on visual materials (i.e. images and video clips) provided by sellers. The goal of AIPVG is to generate videos that are persuasive and have a good viewing experience. AIPVG can be divided into three steps: 1) visual material understanding; 2) visual storyline generation; and 3) post-production.